Adaptive reuse in the healthcare industry: repurposing abandoned buildings to serve medical missions - James K. Elrod; John L. Fortenberry (BMC, 2017)
Abstract Background Adaptive reuse-the practice of identifying, acquiring, renovating, and placing back into service a building or similar structure for a purpose different than that for which it was originally designed-offers great potential for addressing the spatial expansion needs of healthcare establishments in a unique and mutually beneficial manner. This repurposing approach, however, has received very little attention in the health sciences literature, diminishing the opportunities of those serving in hospitals, medical clinics, and related care providing institutions to acquire an understanding of the practice. Discussion The delivery of healthcare services primarily is site based, requiring physical space for physicians, nurses, administrators, and others to carry out the many duties associated with the provision of medical care and attention. But this space often represents a significant expenditure, consuming financial resources which otherwise could be directed toward patient care. Economies on this front are possible through adaptive reuse, permitting more resources to be directed toward mission fulfillment activities. This article directs attention toward adaptive reuse by profiling Willis-Knighton Health System's associated experiences and implementation strategies. Among other things, opportunities and obstacles are discussed, detailed cases are presented, and an operational framework is provided, permitting healthcare providers to understand and make use of this novel practice for addressing spatial expansion needs more affordably. Conclusions Since space considerations exist throughout the lives of healthcare establishments, providers must ensure an awareness of methods for productively attending to these requirements. Evidenced by Willis-Knighton Health System's associated experiences and outcomes, adaptive reuse presents an option for more economically addressing spatial requirements, fostering opportunities to expand the delivery of health and medical services.